Morphometric study of length and grooves of lower central incisors roots - Paulo Roberto Lisa SANCHEZ; Carmen Mueller STORRER; Giuseppe Alexandre ROMITO; Francisco Emílio PUSTIGLIONI (Revista Sul-Brasileira de Odontologia, 2010)
Introduction: Root grooves are considered a risk factor for periodontal disease. The purpose of this study was to measure the length of the root of lower central incisors (LCI), as well as the width and depth of the concavities of their proximal surfaces. Material and methods: The width and depth of root concavities, as well as root length, were evaluated in 90 LCI. All teeth were measured using a digital contour measuring instrument (Contracer®) for the root grooves and a digital calliper for evaluating root length. Results: After statistical analysis (t-Student and Kruskal-Wallis Anova tests, p<0.05) it was possible to confirm: the mean root length on its distal surface (13.88 ±1.47 mm) and on its mesial surface (13.76±1.50 mm). Concavities were present in 100% of the samples; concavities were found 2 mm, coronally from the CEJ, at the CEJ, and at all root surface. The concavities were wider than deeper; on the mesial surface, the greatest width was 1.877 mm and the greatest depth was 0.135 mm; on the distal surface the greatest width was 1.717 mm and the greatest depth was 0.118 mm. Conclusion: The distal surface of the lower central incisor is the longest. The root concavities on the proximal surfaces are present in 100%; the greatest width and depth was at 6 mm apically from the CEJ at both sides, which corresponds to the root middle third. One must get acquainted to the morphological variations of roots to enhance diagnosis, prognosis and treatment.